(untitled) (International Journal of Contemporary Security Studies, 2023)
The paper presents the book "Power and Force" in order to highlight the importance of strategic thinking both in earlier historical periods and in current international events and processes. Special emphasis is placed on the position of the Republic of Serbia in international politics and on the main security risks and threats it faces both in history and in the present. The Republic of Serbia destine for military neutrality as a strategic response to the mentioned risks and threats. Also, the military neutrality of other European countries was analyzed as well as the reasons that led to their success or failure. Based on this analysis, numerous dilemmas emerged, numerous questions remained unclear, but on the other hand, certain lessons were learned. All this enabled a more precise consideration of the military neutrality issues of the Republic of Serbia, primarily the potential problems it will encounter and the potential outcomes.